Extractability, Distribution Among Different Particle Size Fractions, and Phytotoxicity of Cu and Zn in Composts Made With the Separated Solid Fraction of Pig Slurry - Clemente, Rafael; Sáez-Tovar, José Antonio; Bernal, Maria Pilar (Frontiers in Sustainable Food Systems, 2020)
The presence of elevated concentrations of heavy metals (Cu and Zn) in pig slurry and, particularly, in the solid fraction obtained after solid-liquid separation is a limiting factor for their use in agricultural soils. These metals are further concentrated if compost is produced from solid pig slurry. This paper studies the influence of the composting of the separated solid phase of pig slurry on the concentrations and solubility of Cu and Zn, and their distribution in the different particle size fractions, as well as evaluating their potential toxic effects on seed germination and seedling growth. Two composts were prepared with the solid fraction of pig slurry in a piglets and sows farm, using two different bulking agents (cereal straw and cotton gin waste). The concentrations of Cu and Zn in the mature compost were higher due to organic matter degradation; however, their solubility decreased from 0.72 and 1.76 % in the solid fraction of pig slurry to 0.18 and 0.30 % of total Cu and Zn, respectively, in the compost prepared with cotton gin waste. Zinc was concentrated in the smallest particle size fraction, while the Cu concentration was highest in the largest particles, and associated to the organic matter/humic fraction. The elimination of the smallest particle size fraction would not reduce significantly the total heavy metal concentration of the composts. Nevertheless, the low solubility of both metals in the composts avoided any significant toxic effect on seed germination and also in the growth test when compost was present at low rates.